UPAYA MENINGKATKAN SOSIAL EMOSIONAL ANAK MELALUI PERMAINAN BAKIAK DI KELOMPOK B KB NURUL YAQIN WRINGIN ANOM ASEMBAGUS SITUBONDO - Lailatul Islamiyah; Suyanti Suyanti (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2020)
The emotional social development of children is important to develop due to their self-confidence, independence and initiative. Children's emotional social development can be developed through clogs. The purpose of this study is to determine the implementation and results of clogs in an effort to improve children's social emotional. The type of research used is Classroom Action Research (CAR) on group B students at KB Nurul Yaqin Wringin Anom Asembagus Situbondo. The study was conducted in a cycle, which is each cycle consisting of planning, action, observation, and reflection with the aim to improve the quality of learning in the classroom. Based on the results of the study, namely the implementation of clogs to improve children's emotional social development at KB Nurul Yaqin includes; The teacher divides the groups, each group consists of 2-3 children according to the capacity of clogs. On the results of the implementation of the activity showed an increase in aspects of social emotional development of children through clogs, namely Pre-cycle, the percentage value reached 37.5%. The average achievement of child indicators is 4.5. After the Cycle I action, the percentage value reaches 75% with the achievement of the indicator being 6. In Cycle II the percentage value reaches 87.5% with the achievement value of the child indicator being 7.5.